Behaviour of expanded slate semi-lightweight SCC beams with improved cracking performance and shear capacity. (August 2021) - Omar, Ahmed T.; Hassan, Assem A.A.
Abstract: This study investigated the behavior of semi-lightweight self-consolidating concrete (SLWSCC) and lightweight vibrated concrete (LWVC) beams developed with improved shear capacity and cracking behavior. Fourteen concrete beams were cast with different types of lightweight aggregates (either fine or coarse expanded slate aggregates), total binder contents (550 kg/m 3 and 600 kg/m 3 ), fiber lengths (8 mm and 12 mm), and different fiber volume fractions (0.3%, 0.5%, and 1%). The experimental results were also compared with several code-based equations and selected proposed models from the literature that predict the shear strength of reinforced concrete beams with and without fibers. The inclusion of shorter polyvinyl alcohol (PVA) fibers appeared to have more influence on improving the shear performance and cracking behavior of SLWSCC beams compared to longer fibers. It was also found that using expanded slate fine aggregate exhibited better results in terms of the beams' load-carrying capacity, post-diagonal cracking resistance, and energy absorption capacity compared to using expanded slate coarse aggregate. The highest increases in the shear capacity, deformation capacity, post-diagonal cracking resistance, and energy absorption capacity were observed in LWVC beams, as it was possible to use a higher percentage of PVA fibers (1%) because of the absence of self-compactability restrictions.